ISLAMIC EDUCATION MANAGEMENT AND ITS ROLE IN FORMING A NOBLE PERSONALITY: A REVIEW OF SURAH AL-AHZAB 33:70: Manajemen Pendidikan Islam dalam Membentuk Kepribadian Berprestasi Mulia: Kajian Surah Al-Ahzab 33:70 - Mohammad Nurul Yaqin; Sedya Santosa; Nur Ali Yasin; Muhammad Fakhri Salim Kavabih (Transformatif, 2025)
Islamic education management must always be responsive to innovations that align with the developments of the times so that it can continue to provide greater benefits. The Islamic education system is based on the Qur'an and Hadith as the primary sources, which not only impart knowledge but also guide humanity toward a better life, both in this world and in the hereafter. Therefore, every educational institution needs to implement the principles of Islamic education management in its operations. The fundamental principles of Islamic education that must be considered to achieve the desired goals include the implications and characteristics of the community, integration, balance, universality, and dynamism. This study was conducted to explore in depth how the principles of Islamic education management can shape a noble character, with a special focus on Surah Al-Ahzab 33:70, through both textual and contextual analysis. This issue is addressed through library research, using primary data sources from the Qur'an, particularly Surah Al-Ahzab 33:70. Secondary data were taken from tafsir (interpretation) books, while other supporting sources were books and writings relevant to the research topic. The research findings show that the principles of Islamic education management discussed in this study have a significant impact on the formation of noble character, which includes aspects of human behavior and character towards God, oneself, others, and the environment. From the perspective of Surah Al-Ahzab 33:70, these principles play an important role in a person's life. The honesty internalized in Islamic education management encourages all actions toward positive outcomes, contributes to progress, and provides significant contributions to various existing plans.